Efficacy of Fungicides against Soil Borne and Grapevine Pathogens under In vitro Conditions - Singh, Anjali; Thosar, Ratna U.; Chavan, Vijayshree; Saha, Sujoy (International Journal of Bio-resource and Stress Management, 2021)
In vitro bio-efficacy of the novel copper (NC101 and NCP102) and phosphonate (PN103 and PMN104) based fungicides against various soil borne and grape vine pathogens was evaluated at ICAR-National Research Centrefor Grapes, Pune, Maharashtra, India during February - April 2021. The fungicides were screened against five bacterial pathogens viz. Xanthomonas campestris pv. citri, X. campestris pv. campestris, X. campestris pv. punicae, X. campestris pv. viticola and X. oryzae pv. oryzae and 10 fungal pathogens viz. Rhizoctonia bataticola, Sclerotium rolfsii, Cladosporium sp, Alternaria alternata, Colletotrichum gloeosporioides, Penicillium notatum, Magnaporthe oryzae, Fusarium oxysporium, Macrophomina phaseolina (Soyabean isolate)and Macrophomina phaseolina (Jute isolate) at different concentrations. Results indicated that among all the tested fungicides viz. NC101, NCP102, PN103 and PMN104, phosphonate based fungicides (PN103 and PMN104) were highly effective against bacterial isolates with zone of inhibition ranging between 8.75 - 31.12 mmin which X. campestris pv. viticola was found to express least inhibition zone. In case ofpathogenic fungal isolates, similar trend was observed, most of the isolates showed cent percent inhibition at higher concentration of PN103 and PMN104. However Sclerotium rolfsii showed least or no inhibition when tested at different concentrations of fungicides. The chemicals exhibited wide range of inhibition and it was found to increase steadily with increase in concentrations of the test fungicides.